2012
DOI: 10.1177/1545109712453937
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Assessment and Risk Reduction Strategies in the Context of Prevailing Gender Norms in Rural Areas of Cabo Delgado, Mozambique

Abstract: Since minimal information exists on how individuals work within existing social norms to reduce HIV risk, this study explored the specific factors influencing men and women to reduce their HIV risk in the face of prevailing gender norms in rural villages of Cabo Delgado, Mozambique. Qualitative data were gathered from 160 participants through 29 in-depth interviews to explore gender norms, HIV risk determinants, and risk reduction responses. Results were analyzed using adaptations of grounded theory and consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Participants who reported that they did not know whether their primary partner had ever been tested for HIV had a higher risk of HIV infection as well as late diagnosis of HIV in multivariable analyses. These findings contribute to the growing literature on how gender norms may influence sexual risk taking behaviors and risk reduction efforts in Mozambique [18][20] and suggests that HIV testing of couples might be an effective prevention strategy.…”
Section: Discussionsupporting
confidence: 54%
“…Participants who reported that they did not know whether their primary partner had ever been tested for HIV had a higher risk of HIV infection as well as late diagnosis of HIV in multivariable analyses. These findings contribute to the growing literature on how gender norms may influence sexual risk taking behaviors and risk reduction efforts in Mozambique [18][20] and suggests that HIV testing of couples might be an effective prevention strategy.…”
Section: Discussionsupporting
confidence: 54%
“…Sexual relationships that occur between two people of different age brackets is a risk factor as seen from the results and it is common in many parts of the world [17,18]. Usually, these relationships are embraced for the benefit of material support and other gains to the women and for pleasure to the men [27].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, women living in rural areas are marginalized and disempowered and face geographical barriers in terms of accessing HIV knowledge and other HIV services [16]. Younger women married to older men do not have equal say in discussing safe sex practices [17,18]. In addition, the risk of HIV acquisition is also known to be high among cohabiting or married couples especially when one of the partners is HIV positive [19] or where intimate partner violence exists [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Women living in rural areas are marginalized and disempowered, and face geographical barriers in terms of accessing HIV knowledge and services [13]. In rural communities, the deeply entrenched beliefs about the role and position of women in society [3,4,11] place marriage as an important risk factor for HIV infection among women [4].…”
Section: Introductionmentioning
confidence: 99%